2021
DOI: 10.1177/03635465211018636
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Pure Platelet-Rich Plasma Therapy for Adhesive Capsulitis: A Bed-to-Bench Study With Propensity Score Matching Using a Corticosteroid Control Group

Abstract: Background: While platelet-rich plasma (PRP) has been widely studied for musculoskeletal disorders, few studies to date have reported its use for adhesive capsulitis (AC). Fully characterized and standardized allogenic PRP may provide clues to solve the underlying mechanism of PRP with respect to synovial inflammation and thus may clarify its clinical indications. Purpose: To clinically evaluate the safety and efficacy of a fully characterized pure PRP injection in patients with AC and to assess the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 63 publications
(96 reference statements)
0
21
0
Order By: Relevance
“…[30] This supports the wider use of growth and regenerative factors in tendinopathies aiming at rapid repair and functional improvement. [13,24,32,37] Conclusion L-GF injection in patients with SIS resulted in signi cant improvement in pain and disability according to the improvement in shoulder range of movement, painful arc sign, VAS, SPADI, as well as signi cant reduction in the thickness of the supraspinatus tendon as measured by ultrasound compared to the saline group.…”
Section: Discussionmentioning
confidence: 88%
“…[30] This supports the wider use of growth and regenerative factors in tendinopathies aiming at rapid repair and functional improvement. [13,24,32,37] Conclusion L-GF injection in patients with SIS resulted in signi cant improvement in pain and disability according to the improvement in shoulder range of movement, painful arc sign, VAS, SPADI, as well as signi cant reduction in the thickness of the supraspinatus tendon as measured by ultrasound compared to the saline group.…”
Section: Discussionmentioning
confidence: 88%
“…This supports the wider use of growth and regenerative factors in tendinopathies aiming at rapid repair and functional improvement. [ 13 , 24 , 32 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this group, P-PRP decreased pain and improved shoulder ROM and function comparable to CS. Moreover, they found that P-PRP decreased proinflammatory cytokines only during the inflammatory phase of the condition ( 64 ).…”
Section: Prp In Adhesive Capsulitismentioning
confidence: 99%
“…Based on the evidence of these studies, the use of the PRP is supported in the diagnosis of AC ( 61 , 62 , 63 , 64 , 65 , 66 ). Nevertheless, there are limitations of these studies.…”
Section: Prp In Adhesive Capsulitismentioning
confidence: 99%
See 1 more Smart Citation